(untitled) (Zoo Botanica, 2025)
Onion thrips, Thrips tabaci L. is an economic pest of onion in worldwide. To control this noxious pest, different controlling methods are introducing every day. The present research is also contributing in thrips control. Dried leaves of banana, sugarcane, and rice were used as mulching material on onion field at two different climates arid and semi-arid in the same season. Thrips populations were recorded weekly-basis from both areas. Overall, the results showed that mulching with banana leaves was effective in both arid and semi-arid areas, followed by mulching with sugarcane and rice leaves. All treatments in semi-arid zone showed the lowest thrips population (banana leaves 3.50 ±0.32, sugarcane leaves 4.40 ± 0.33, rice leaves 5.53 ± 0.39 and control 11.40 ± 0.69) as compared to arid zone (banana leaves 8.23 ± 0.61, sugarcane leaves 9.93 ± 0.59, rice leaves 10.50 ± 0.61 and control 18.77 ± 1.01). Banana leaves can hold more water and keep soil moist for long time, as thrips prefer hot and dry climate, so the moist field prevent thrips population. Using such plant residuals can help to control thrips, as it is burned in most of the fields and there are no further uses of these materials.